Russian Folk Music Interaction in Tchaikovsky’s Works and First Piano Concerto - Tuğrul Adiloğlu (Konservatoryum)
This study aims to investigate the composer Pyotr Ilyich Tchaikovsky’s ties with Russian Folk Music and to examine the reflections of these ties in his Piano Concerto No. 1. Tchaikovsky is one of the composers whose life story and works are frequently discussed in books, theses and articles. In biographical texts, according to the available data, the process of creating composers’ works and their sources of inspiration can also be conveyed. The elements of the geographies in which they live and the social culture of these geographies can be included as motifs reflected in the works of artists. Folk music, which is one of the effective carriers of cultural elements, has been identified as the elements that inspired composers in many periods of history in the light of documents and information obtained in retrospective research. In this study, which was conducted by reviewing sources that provide information about Tchaikovsky’s life story and works, findings on the composer’s interaction with folk music are presented.